Maido “Umbai Cacing” Kebudayaan Jawa yang Membusuk - Bagus Riyono; Yurisa Nurhidayati (Faculty of Psychology, Universitas Gadjah Mada, 2011)
“Maido” is a peculiar term within Javanese language which meaning is so unique that it has no perfect translation to Indonesian language. It has a mix meaning of denial, rejection,apathetic, or put others down. However, on the positive side, “maido” could mean as an attitude of critical thinking. This study aims to uncover the position of “maido” withinJavanese culture, whether it is one of the local wisdom which supposed to be positive or is it a “cultural accident” that need to be reconsidered. In general the purpose of this study is to understand the meaning and the origin of “maido” attitude within Javanese people. By knowing that, it is expected that the academiciancould treat it proportionally as a part of the psychology of Javanese culture. The method applied to this study is phenomenology as a qualitative approach. Respondents of the studyconsist of the experts of Javanese culture and observers of the culture. The result shows that “maido” does not have a central position in Javanese culture, and the positive meaning is fading away. Currently “maido” is known as a negative attitude thatis not supposed to be shown.